Democracia y desplazamiento durante la guerra civil colombiana - Steele, Abbey, 1979- (Universidad del Rosario, 2020)
This is one of few books available in English to provide an overview of the Colombian civil war and drug war. Abbey Steele draws on her own original field research as well as on Colombian scholars' work in Spanish to provide an expansive view of the country's political conflicts. Steele shows how political reforms in the context of Colombia's ongoing civil war produced unexpected, dramatic consequences: democratic elections revealed Colombian citizens' political loyalties and allowed counterinsurgent armed groups to implement political cleansing against civilians perceived as loyal to insurgents. Combining evidence collected from remote archives, more than two hundred interviews, and quantitative data from the government's displacement registry, Steele connects Colombia's political development and the course of its civil war to purposeful displacement. By introducing the concepts of collective targeting and political cleansing, Steele extends what we already know about patterns of ethnic cleansing to cases where expulsion of civilians from their communities is based on nonethnic traits.